The Portuguese, Dutch and Africans in Angola during the sixteenth and seventeenth centuries: The making of a colonial territory - (:unkn) unknown (My University, 2016)
This thesis aims to question the nature of the Portuguese presence in Angola during the 16th and 17th centuries, a period which corresponds to the rise of the transatlantic slave trade in the South Atlantic Ocean. We pay particular attention to the distinctive features of the Portuguese presence: firstly, we insist on its territorial nature, that differentiates it from other African areas where Europeans went no further than setting up trading posts on the coastline; secondly, we focus on the Luso-Dutch rivalry that took place during the first half of the 17th century, leading to one of the first intra-European confrontations on sub-Sahara African soil.The first four chapters address the question of the colonial territory: they cover the period from 1483, when the Portuguese reached the mouth of the Congo River, to 1671, date of the decisive Portuguese victory over the Ndongo kingdom for the control of the Luanda hinterland. We analyse the stages in the formation of this territory by focusing on the interactions between African and European political powers. This focus leads us to take a special interest in the colonial powers' attempts at delimiting the colonial territory, a delimitation based on both the action of the colonial agents and the production of new geographical knowledge. In the fifth and final chapter, we analyse the social dynamics and characteristics of the agents that constitute what we see as a new emerging colonial society.
Keywords: African Research